Kurikulum Pendidikan Islam Dan Tantangan Dinamika Peradaban Global (Sebuah Pendekatan Paradigmatik) - Imam Mawardi (At-Tajdid: Jurnal Ilmu Tarbiyah, 2017)
Curriculum of Islamic education is the prominent alternative in addressing the various issues arising along with the dynamic change of global civilization. This is due to the common ground of the problem of Islamic education and the needs in facing civilization challenge, in which each concept will evolve to adjust global logic that tends to be pragmatic. Through Islamic education curriculum, in depth study about how the scientific structure should be reconstructed and well developed can be done to meet the needs of the community. The first, the role of curriculum in the clash between the ideas and the pragmatic needs can be divided into three roles are integrated, the conservative role, the role of the creative, and critical roles/ evaluative. Second, the meaning of universal values ​​and disciplines of Islamic education is required to play its role in a dynamic and proactive through the process of transformation of moral values ​​in the access to fortify themselves from the negative globalization. Third, the paradigm of Islamic education curriculum in addressing the problems and future-oriented global civilization, namely the rebuilding spirit curriculum with the basic values ​​of Islam, either in the form of a written curriculum and of the hidden curriculum. Therefore, it is necessary to pay attention to the major issues in designing the curriculum, namely how to set a strong foundation of curriculum (religious, philosophical, psychological, sosio-cultural, and development of science and technology); how to formulate the objectives; how to define the instructional procedure based on the learning materials studied with the appropriate methods and media; how to implement the curriculum in teaching and learning process; and how the curriculum evaluation be done comprehensively.